1981
DOI: 10.1159/000275520
|View full text |Cite
|
Sign up to set email alerts
|

Cochleo-Saccular Degeneration in One of Three Sisters with Hereditary Deafness, Absent Gastric Motility, Small Bowel Diverticulitis and Progressive Sensory Neuropathy

Abstract: This is a report of cochleo-saccular degeneration found in temporal bones from a patient who had suffered from slowly progressive and total sensorineural deafness which had an inherited origin. At age 8, this patient began to complain of hearing loss, and by age 10 she was totally deaf. The patient was 1 of 3 female siblings who have suffered from an exactly identical progressive disease: deafness, absent gastric motility, small bowel diverticulitis and ulceration, and sensory neuropathy. The temporal bone pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Chromosomal studies had confirmed trisomy 21. The right organ of Corti was 28.7 mm long, with lateral semi¬ circular canal measurements as follows: A, 6.99 mm; B, 1.73 mm; and C, 1.97 mm. The left cochlea was 28.2 mm long, and the lateral canal measurements were as fol¬ lows: A, 7.52 mm; B, 2.00 mm; and C, 1.85 mm.…”
Section: Histopathologic Findingsmentioning
confidence: 99%
“…Chromosomal studies had confirmed trisomy 21. The right organ of Corti was 28.7 mm long, with lateral semi¬ circular canal measurements as follows: A, 6.99 mm; B, 1.73 mm; and C, 1.97 mm. The left cochlea was 28.2 mm long, and the lateral canal measurements were as fol¬ lows: A, 7.52 mm; B, 2.00 mm; and C, 1.85 mm.…”
Section: Histopathologic Findingsmentioning
confidence: 99%
“…1). Studies related to cochleosaccular degeneration discussed its influence in a variety of animal models (mouse [8],cats [9], dogs [10, 11], mink [12]) and human [13].
Fig.
…”
Section: Introductionmentioning
confidence: 99%